Q&A - Ask Doubts and Get Answers
Q

Solve the following linear equation. m - (m-1)/2 = 1 - (m-2)/3

Solve the following linear equation.

Q.6    

               m - \frac{m-1}{2} = 1 - \frac{m-2}{3}

Answers (1)
Views

We have

                            m - \frac{m-1}{2} = 1 - \frac{m-2}{3}

Multiplying both sides by 6 (as it is LCM of the denomenator.)

                           6m - 3(m - 1)  = 6 - 2(m - 2)

or                       6m - 3m + 3 = 6 - 2m + 4

or                              3m + 3 = 10 - 2m

Transposing -2m to the LHS and 3 to the RHS:

                              3m + 2m = 10 - 3 

or                              5m = 7

                                m = \frac{7}{5}

Exams
Articles
Questions